TSI Finders for Estimation of the Location of an Interference Source Using an Ariborne Array. (6th February 2008) - Madurasinghe Madurasinghe, Dan Dan; Shaw Shaw, Andrew Andrew
Abstract : An algorithm based on space fast time adaptive processing to estimate the physical location of an interference source closely associated with a physical object and enhancing the detection performance against that object using a phased array radar is presented. Conventional direction finding techniques can estimate all the signals and their associated multipaths usually in a single spectrum. However, none of the techniques are currently able to identify direct path (source direction of interest) and its associated multipath individually. Without this knowledge, we are not in a position to achieve an estimation of the physical location of the interference source via ray tracing. The identification of the physical location of an interference source has become an important issue for some radar applications. The proposed technique identifies all the terrain bounced interference paths associated with the source of interest only (main lobe interferer). This is achieved via the introduction of a postprocessor known as the terrain scattered interference (TSI) finder.